Sustentabilidade em comunidades rurais: um estudo do assentamento Maceió, Itapipoca-CE - Monteiro, Alexandra Pedrosa (2018)
Capitalism caused the Advancement Several consequences the environment, causing social imbalances, Environmental, Economic and Institutional. The first studies on the impacts of this development to natural resources began in the late twentieth century, culminating in a widespread concept: sustainable development. They emerged several tools that seek to measure sustainability through indicators, in order to support public policies and monitor the system's sustainability. Thus, the aim of this study is to evaluate the sustainability of the settlement Maceio, located in Itapipoca - CE, through the dimensions used for sustainable development, namely economic, environmental, social and institutional. For this are selected indicators that characterize these dimensions, which made it possible, with the results to identify the strengths and weaknesses of the settlement from the point of view of sustainability. The methodology adopted is composed by a bibliographical survey, field research, with the collection of data through the application of forms and the creation of indicators and indexes, using Multivariate Analysis.